A national quality framework for early childhood education and care a discussion paper - Council of Australian Governments. Productivity Agenda Working Group. Early Childhood Development Sub-Group. ([Canberra?] : COAG Productivity Agenda Working Group, Education, Skills, Training and Early Childhood Development, 2008)
"This discussion paper provides the basis for the initial round of consultations on the development of a new national quality framework for early childhood education and care to progress these reforms. The consultations will be based on the key questions outlined in this paper and will be used to inform the development of the framework. In addition written submissions are also welcome."
"1 August 2008"
Title from pdf file title screen (viewed on 13 Oct. 08 )
Includes bibliographical references.
Text.
Mode of access : Internet via World Wide Web. Available at: http://www.dest.gov.au/sectors/early_childhood/policy_initiatives_reviews/coag/documents/discussion_pdf.htm
System requirements: Adobe Acrobat reader to view PDF file.
Keywords: Child care services -- Government policy -- Australia; Child care -- Government policy -- Australia; Early childhood education -- Government policy -- Australia; Early childhood education -- Australia